Quantification of Polycyclic Aromatic Hydrocarbons in Wetlands in Aja-Pessu and Environs (Oil Bearing Communities) Warri South Delta, Nigeria - C. Ogwu; V. Ideh; J. Ogana; O. M. Adinkwu (Journal of Applied Sciences and Environmental Management)
Oil production in Nigeria is synonymous with wetland degradation resulting in most times in youth’s restiveness and unrests in oil bearing Niger Delta. Hence, the objective of this paper is to evaluate the quantification of polycyclic aromatic hydrocarbons in wetlands in Aja-Pessu and environs (oil bearing communities) Warri South Delta in Nigeria using appropriate standard methods. The mean results obtained were: pyrene 1.06±0.11 μg/l, chrysene 1.05±0.00 μg/l , BaP; 1.05±0.10 μg/l, BaA; 1.05±0.01 μg/l and BbF 1.06±0.11 μg/l. The results obtained were subjected to test of significance with ANOVA deploying SPSS IBM model 29 at 0.05 level of significance and the p value was 0.045, thus rejecting H0. The study concluded that the wetlands in Aja-Pessu and environs are polluted with PAHs investigated higher than EU 1881/2014 MPC, thus the produce will neither be fit for human nor animal consumption and will equally not be fit for export. The study recommended that oil companies operating in the settlement should adopt world best practices in their operations, the monitoring agencies NESREA and NOSDRA should be made to carry out their assignment expeditiously and the impacted wetlands should be remediated and restored for adoption of pen aquaculture for job creation in Nigeria.